Understanding the Pancreatic Islet Microenvironment in Cystic Fibrosis and the Extrinsic Pathways Leading to Cystic Fibrosis Related Diabetes. (October 2021) - Al-Selwi, Yara; Shaw, James AM; Kattner, Nicole
Cystic fibrosis (CF) is an autosomal recessive chronic condition effecting approximately 70 000 to 100 000 people globally and is caused by a loss-of-function mutation in the CF transmembrane conductance regulator. Through improvements in clinical care, life expectancy in CF has increased considerably associated with rising incidence of secondary complications including CF-related diabetes (CFRD). CFRD is believed to result from β-cell loss as well as insufficient insulin secretion due to β-cell dysfunction, but the underlying pathophysiology is not yet fully understood. Here we review the morphological and cellular changes in addition to the architectural remodelling of the pancreatic exocrine and endocrine compartments in CF and CFRD pancreas. We consider also potential underlying proinflammatory signalling pathways impacting on endocrine and specifically β-cell function, concluding that further research focused on these mechanisms may uncover novel therapeutic targets enabling restoration of normal insulin secretion.